STUDI DAMPAK PEMBELAJARAN IPA VIA DARING TERHADAP PELAKSANAAN PRAKTIKUM DI SEKOLAH MENENGAH PERTAMA - Youshinta Ariani; Wahono Widodo (Jurusan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2022)
Online learning during a pandemic will certainly affect the practicum implementation process, one of which is due to inadequate facilities and infrastructure. The purpose of this study was to determine the impact of online science learning on the implementation of practicum in several East Java junior high schools. This research used surveyo research with descriptive method (interviews and questionnaires). The results of this study indicate that the impact of online learning in science practicum activities is the implementation of practicum activities carried out individually in their respective homes through supporting applications. The explanation of the practicum activities is carried out directly by the teacher through Google Meet/Zoom and the teacher also provides a practicum module or student worksheets during the practicum. Applications used during online practicum activities include Zoom, Google Meet, Micorsoft 365, Microsoft Forms, Microsoft Sway, PhET Simulations, and WhatsApp. Another consequence of online learning is the online reporting of practicum activities in the form of videos and portfolio sheets. After collecting the practicum report, the teacher gives an evaluation at the next meeting. The positive impact of online practicum activities is increasing independent learning skills, creativity, and digital literacy. Obstacles in the implementation of online practicum are limited tools and materials, teachers cannot guide directly, and practicum methods are not varied. This causes some materials to be unable to conduct the practicum and students are less able to understand the practicum well.